Evaluation for the effects of nutritional education on Chinese elite male young soccer players: The application of adjusted dietary balance index (DBI) - Dan Zeng; Zi-Long Fang; Lu Qin; Ai-Qi Yu; Ying-Bin Ren; Bo-Yang Xue; Xin Zhou; Zi-Yu Gao; Meng Ding; Nan An; Qi-Rong Wang (Journal of Exercise Science & Fitness, 2020)
Objectives: To evaluate the effect of nutrition education on Chinese elite male young soccer players through the knowledge, attitude, behavior (KAP) survey and an adjusted dietary balance index (DBI). Methods: 30 Chinese elite male young soccer players were randomly divided into two groups: lecture group (N = 15, Age: 16.7 ± 1.8 years, Height: 173.9 ± 9.0 cm; Weight: 62.4 ± 13.0 kg; Training years: 5.6 ± 2.7 years) and non-lecture group (N = 15, Age: 16.8 ± 1.7 years, Height: 175.5 ± 7.9 cm; Weight: 62.5 ± 12.3 kg; Training years: 6.2 ± 3.3). The comics book was given to the non-lecture group, while the a four-week nutritional quality education along with comic books were given to the lecture group. Before and after 4 weeks nutritional education, dietary nutritional status of both groups was assessed. The main outcome measurements included the scores for each part of the KAP survey, diet status (food-weighing method) and the dietary index in the adjusted DBI-07 system (DBI-low bound score, LBS; DBI-high bound score, HBS; and DBI-diet quality distance, DQD). Results: In the lecture group, significant differences were found in the scores of general nutrition knowledge, sports nutrition knowledge and total scores of KAP dietary questionnaire after 4 weeks nutritional education (P < 0.01). However, there is no significant difference in dietary attitude and dietary behavior (P > 0.05) on both two groups. There is no significant change in the DBI-low bound score (LBS), DBI-high bound score (HBS) and DBI-diet quality distance (DQD) of dietary quality index (P > 0.05) in both two groups. Conclusions: Four weeks nutritional quality education improved the understanding of dietary nutrition among Chinese elite male young soccer players. Keywords: Adolescent, Athletes, Nutrition, Health promotion